A conceptual model of sustainable supply chain management in small and medium enterprises using blockchain technology - Gurudutt Nayak; Amol Dhaigude (Cogent Economics & Finance, 2019)
This paper proposes a conceptual model of sustainable supply chain management (SSCM) in small and medium enterprises (SME) using blockchain technology (BT). With growing focus on sustainable business process, research on SSCM is gaining prominence. BT, being a disruptive technology, has potential to impact the SSCM. Using the extant literature, the antecedents of SSCM using BT have been identified. Multiple-criteria decision-making has been deployed to develop the conceptual model. Various managerial and theoretical implications along with scope for future research have been discussed.
Keywords: M15; M11; M10; 330; sustainable supply chain management; blockchain technology; triple bottom line; sustainability; supply chain performance; conceptual model